MANAJEMEN PROGRAM PENDIDIKAN KESETARAAN PAKET C DI HOMESCHOOLING PUTRAGAMA SEMARANG - Dwi Hari Astuti; Ilyas Ilyas (Universitas Tribhuwana Tunggadewi, 2024)
The purpose of this study determines and describes (1) the management of package C equivalency education program which includes planning, organizing, implementing, and supervising, and (2) the supporting and inhibiting factors in the management of package C equivalency education program at Homeschooling Putragama Semarang. The research method is descriptive qualitative with data collection by observation, interview, and documentation. Data validity test with triangulation of sources and techniques. The results showed (1) management includes (a) planning; setting goals; program objectives; teaching materials, methods and media; tutor qualification standards; time and place of implementation; and funding sources, (b) organizing, including division of tasks and responsibilities; preparation of organizational structures; and preparation of facilities, (c) implementation, including providing motivation; teaching materials; methods; media; materials and learning schedules, and (d) supervision, internal and external. (2) Supporting factors of the program are the managers, staff, and tutors who can work well together, are cooperative, solid, and competent in carrying out their duties, in addition to the presence of psychological services and parents who are also cooperative. Meanwhile, the inhibiting factors are students who lack discipline in participating in learning activities.